Disfunção erétil psicogênica e acupuntura: uma opção terapêutica? - Schiavo, Fúlvio (2006)
This work was elaborated on a literature review about the Acupuncture practice in the treatment of psychogenic erectile dysfunction. The erectile dysfunction is defined and inserted in the sexology context. Its aetiology, risk factors and alternatives for treatment are briefly discussed. The Acupuncture, a new Western therapeutic aid, is approached in the field of the Traditional Chinese Medicine. Due to the differences in the way of facing the sexuality between the Western and the Eastern cultures, and the possibility of approaching at the same time the physical and psychological aspects of diseases, the Acupuncture was evaluated in some studies as an option for the treatment of the psychogenic erectile dysfunction. The articles are clinic test types, retrospective study, case report and review. Taking into account the ones with better outline, the results showed that the acupuncture was efficient in about 60 to 70% of the cases. Although these results are promising, the papers have some structural failure and they do not have part of the information related to the intervention strategy (handling of the needles). Therefore, it is suggested that further studies dealing with this subject ought to be more feasible. Up to end of this research, there was not sufficient information to provide the effectiveness of Acupuncture in the treatment of the psychogenic erectile dysfunction.